Bone, dentin and cementum differentially influence the differentiation of osteoclast-like cells - Annika Both; Ghosn Ibrahim; Jana Marciniak; Birgit Rath-Deschner; Erika Calvano Küchler; Christian Kirschneck; Lina Gölz; Andreas Jäger; Svenja Beisel-Memmert (Scientific Reports)
Abstract Our aim was to investigate how different oral hard tissues determine the differentiation of osteoclast-like cells. Murine macrophage cells were stimulated for 12 day with RANKL and M-CSF on dentin slices. Morphological changes of cells and hard tissues were examined by electron microscopy and toluidine blue staining. Cells were stimulated with RANKL and M-CSF on pulverized bone, dentin, cementum or polystyrene—with and without stimulation. TRAP staining was performed. To elucidate total gene expression, RNA sequencing was carried out. Four target genes (CXCL2, IGF-1, GDF15, HSPA1b) were selected and their expression was analyzed by RT-PCR and ELISA. Statistics comprised One-way ANOVA and Tukey’s test (P < 0.05). Stimulation induced differentiation of mouse macrophages into TRAP-positive osteoclast-like cells forming resorption pits on dentin. Gene expression analysis revealed that 1930, 446 and 87 genes were differentially regulated by cultivation on cementum, bone or dentin respectively compared to polystyrene. Culture on bone or dentin caused CXCL2 upregulation. In all stimulated groups IGF-1 was downregulated while GDF15 expression was elevated in cultures on dentin. Cultivation of cells on cementum resulted in an upregulated HSPA1b expression. Our results indicate that extracellular matrix of different oral hard tissues plays an important role in differentiation processes of osteoclast-like cells.